Socioeconomic class, status group and social origin in Athens c.2013 - A structural schema for the analysis of urban consumption - Εμμανουήλ, Δημήτρης (The Greek Review of Social Research, 2016)
The paper outlines the analytical framework and the empirical correlates regarding the main dimensions of social stratification that were explored through a survey research in 2013 Athens examining the relationship between stratification and consumption – both material and cultural. Focusing on cultural consumption, it is argued that a neo-weberian framework based on a clear-cut distinction between socioeconomic class and social status coupled with social origin data as indicators of cultural capital offers a potent model of structural determinants of consumption patterns. The paper examines the available material for an application of such a model in the Athenian context and offers an example of its relevance for the empirical analysis of cultural and mixed cultural/material consumption in the case of the breadth of choices of theater genres and types of places for dining out.